DISTANCE LEARNING TECHNOLOGIES IN FORMATION OF PROFESSIONAL TRAINING OF FUTURE ENGLISH TEACHER - Gnedkova, O. (Journal of Information Technologies in Education (ITE), 2016)
Due to the global informatization of society and the process of involving information and communication technologies (ICT) in all areas of human activity, including the educational process of high school the problem of new model construction of process of future highly qualified and competitive professionals training is raised. In conditions of Ukraine integration into the European educational space, the significant changes in professional training of teachers in higher education institutions are taken place. ICT and distance learning technologies are implemented in learning process. However, this process causes many difficulties in students and teachers, for example, the lack of guidance on the implementation of ICT and distance learning technologies in the learning process and not enough formed skills and abilities of teachers and students to use ICT and distance learning technologies in professional activity. These problems negatively affect on the quality of future specialists training, including teachers of foreign language (English). To increase the quality of English teachers training there is a need to introduce distance learning technologies in language learning process, at study the discipline “Practical English Course”. On the base of analysis of psychological and educational literature in future English teachers training, the results of international studies and methodological literature of distance learning the practical implementation of distance learning technologies in educational process of training of English teachers of Kherson State University was presented.